COMMUNICATIVE AND MODERN METHODS OF TEACHING ENGLISH (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
This article examines communicative and modern methods of teaching English. It highlights the importance of fostering real-life communication skills and integrating contemporary teaching techniques to enhance language acquisition. Key approaches discussed include task-based learning, technology integration, and student-centered methodologies. The goal is to create engaging and effective learning environments that cater to the needs of today’s learners.